Prevalence of patients at risk for developing obstructive sleep apnea based on the STOP‐BANG questionnaire at King Abdulaziz University Faculty of Dentistry - Maisa O. Al‐Sebaei; Mohamed S. Bamashmous; Mohamed H. Mirdad; Mohammed A. Sindi (Wiley, 2023)
Abstract Objective Obstructive sleep apnea (OSA) is a common sleep disorder. Its susceptibility can easily be detected when it is at an early stage as can patients who are at risk of OSA. A simple questionnaire such as STOP‐BANG (SB) can facilitate early detection. Our study aims to assess the risk of OSA and evaluate its correlating risk factors in patients attending King Abdulaziz University Faculty of Dentistry (KAUFD), Jeddah, Saudi Arabia, using the SB questionnaire. Methods Ethical approval was obtained. A random sample of patients ages 18-80 years, who visited KAUFD between November 2016 and April 2017 were recruited. Three highly trained and calibrated dental interns obtained the following measurements (weight, height, blood pressure, and neck circumference) and administered the questionnaire in a face‐to‐face interview. Results A total of 55 patients (62% females) participated in the study with a mean age of 34.6 years and hypertension reported as 16.4%. According to the SB, 31% of patients were found at high risk of OSA. Large neck circumference (40.22[±4.7] cm) and gender (66% males) were found to be significantly correlated with high‐risk patients; p < .001. Conclusion Approximately one third of the patients were at high risk of OSA, with men and patients having large neck circumference being significantly more affected. Systolic blood pressure, hypertension, and smoking were found to be high in high‐risk patients. However, they were not statistically and significantly different from those patients who were not in high risk. The role of a dentist should be to utilize the questionnaire to detect any patient at risk of OSA and refer them accordingly.